The History of the Sangap Di Jahowa Hymnbook of the Batak Protestant Christian Church (HKBP) - Manik, Toman (Sekolah Tinggi Teologi Trinity Parapat, 2023)
Ende or songs are very important in every church. To develop services in HKBP churches, varied religious songs are needed. This research aims to investigate when the HKBP churches started using Sangap di Jahowa songbook for the first time, and what are the roles of the songbook holds in HKBP services. This research used qualitative method, by interviewing some people who directly related to the arrangement of the book. Data from articles and books as well as theories from interdiciplinary science were also taken into consideration. This research shows that Ende Sangap di Jahowa songbook exists because of the needs of varied songs in addition to Buku Ende and Haluaon na Gok. Its presence shows that for hundred of years HKBP congregations have adapted and created new songs from ones that came out of their own culture. It gives positive changes in HKBP services.